Immigrant Canada : Demographic, Economic, and Social Challenges - Halli, Shivalingappa S., 1952-; Driedger, Leo, 1928- (Book collections on Project MUSE., 1999)
The contributions in this volume reflect a wide variety of research orientations and describe the diversity and complexity of doing research focusing on immigrants who have come to Canada.